A collapsed-cone based transit EPID dosimetry method. (February 2018) - Martínez Ortega, Jaime; Pinto Monedero, María; Gómez González, Nuria; Tolani, Naresh B.; Castro Tejero, Pablo; Castanedo Álvarez, Miguel; Núñez Martín, Luis; Sánchez Montero, R.
Highlights: Developed a transit portal dosimetry method based on Pinnacle 3 . The clinical model in Pinnacle 3 was not modified for this purpose. A virtual phantom with different slabs was introduced in Pinnacle 3 to simulate EPID. Corrections for spectral variations were introduced. Threshold can be established when 95% of the points do not pass the γ (5%, 3 mm) criterion. Abstract: Purpose: To develop a transit-dose portal dosimetry method based on a commercial collapsed-cone algorithm. Methods: A Varian Clinac21EX (Varian Medical Systems, USA), equipped with an amorphous-silicon EPID aS1000, was used. Dose calculations were performed with the collapsed-cone algorithm of Pinnacle 3 v8.0 m (Philips Medical Systems, USA). A model for the energy of 6 MV was made in Pinnacle 3 and afterwards validated for clinical use. A virtual phantom with different densities was contoured and superimposed on the patient images, simulating the presence of the EPID during the treatment. Corrections for photon spectral variations were introduced using Matlab (Mathworks, USA). Transit dosimetry was verified with an anthropomorphic phantom, on which different treatment fields were simulated in locations of skull, thorax and pelvis. In addition, a prostate treatment with IMRT was administered thereon. Dose distributions were compared with gamma index. Results: The dose differences at the central point did not exceed 2%, except for the 20 x 20 cm 2 field size centered in the skull. The model presented in this work, assumes that the dimensions of the solid water phantom, are infinite, except for the thickness. The mean values for the gamma index pass rates were 85.62% for (3%, 3 mm), 91.73% (4%, 3 mm) and 95.68% (5%, 3 mm). Conclusions: The value of 95% for γ (5%, 3 mm) can be established as the value below which the origin of the discrepancies should be investigated. It should be considered that the proposed method is complementary and not a substitute for pre-treatment dosimetry.